The fabrication and characterization of Copper Phosphate nanoparticles (Indian Journal of Chemistry (IJC), 2025)
Copper acetate was treated with phosphoric acid and by using chemical co-precipitation method, copper phosphate nanoparticles were obtained. The method seeks to synthesize Copper Phosphate in the most uncomplicated manner of dimensions of nanoparticle. Different characterization approaches were utilized to identify the synthesized material, revealing the information it may provide or the materials for which it is intended. X-Ray Diffraction, Raman Spectroscopy, -Visible, Scanning Electron Microscopy and Fourier Transform Infrared were utilized to analyze the synthesized nano particle. The stretching and bending frequencies of sample's molecular functional groups are examined using FTIR spectra. When using XRD, the size of the copper phosphate nanoparticles was identified to be 57.74 nm. The obtained product Copper (II) Phosphate has well-crystallized particles, as seen in the SEM image. The UV spectrum notifies the different electronic excitation states of Copper (II) Phosphate. The distribution of Copper (II) Phosphate nanoparticles is appropriate, as indicated by the linear fit. The Raman spectrum's peaks attest to the existence of copper phosphate.